The role of black consciousness in the experience of being black in South Africa: the shaping of the identity of two members of AZAPO - Mnguni, Mphikeleli Matthew (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
The research attempts to understand the role Black Consciousness (BC) plays in the identity of blacks in South Africa by exploring and describing the experience of self-identity in the life-history context of two members of AZAPO, a BC organisation. The literature review explores the work of Biko, Manganyi, and Fanon with a view to understanding whether and how it might be claimed that BC galvanises the black person to discard the crippling fear of colonialism which inflicts feelings of inferiority, and to rise up to claim his/her rightful place in community life. To explore the philosophical assumptions made in the literature review, a qualitative study was conducted. Interviews were conducted with two black adults who have adopted BC philosophy. Three separate in-depth phenomenological interviews were conducted which yielded a description of the experiences of each respondent. A tape recorder was used to record the interviews and they were transcribed for analysis. A thematic analysis was conducted using the reading guide method. The material was thematised using the following questions: What biographical factors are seen as being important prior to the respondent becoming black conscious? How did the participant come to realise his/her self-identity as problematic? How did the process of adopting BC change the participant's selfidentity? The results indicate that participants became aware very early in their lives and prior to adopting BC, that their own supportive and cohesive family cultures were at odds with the surrounding social context. Early experiences of this were initially unintelligible but impressionable. BC in this sense provided a framework for understanding and engaging with these experiences. The study shows that the adoption of BC helped to make sense of experiences of community isolation, discrimination, oppression and provided them with a mode of engaging practically with these issues. It was not adopted from a perspective of poor self-esteem or other such purely personal characteristics which may have been expected on the basis of literature in the area. BC was adopted as a way of understanding the relationship between their communities or backgrounds and the broader social environment and if there was a 'healing' project it was at this level.However, the study did show the close relationship between individual and social well-being that emerged as intrinsic both to the philosophy of BC and the lives of these individuals. This was shown to play out in the commitment of these individuals to the development of black communities and in their tying of their own destinies to the destiny of the oppressed black people in general. These and other issues which emerged in the two case studies are discussed in relation to the literature in the area.
Keywords: Black consciousness; Azanian People's Organization; Identity (Psychology)